A prospective observational study of a novel 2-phase infusion protocol for the administration of acetylcysteine in paracetamol poisoning. (7th February 2016) - Isbister, Geoffrey K.; Downes, Michael A.; Mcnamara, Kylie; Berling, Ingrid; Whyte, Ian M.; Page, Colin B.
Abstract: Context : The current 3-phase acetylcysteine infusion for paracetamol poisoning delivers half the dose over 15–60 min and frequently results in adverse reactions.Objective : We aimed to determine adverse reaction frequency with a modified 2-phase infusion protocol with a longer initial infusion.Materials and methods : A prospective observational study of a modified 2-phase acetylcysteine protocol was undertaken at two hospitals. Acetylcysteine was commenced on admission and ceased if paracetamol concentrations were low-risk (below the nomogram line). The first infusion was 200 mg/kg over 4–9 h based on ingestion time or 4 h for staggered/chronic ingestions. The second infusion was 100 mg/kg over 16 h. Pre-defined outcomes were frequency of adverse reactions (systemic hypersensitivity reactions or gastrointestinal); proportion with alanine transaminase (ALT) > 1000 U/L or abnormal ALT.Results : 654 paracetamol poisonings were treated with the new protocol; median age 29 y (15–98 y); 453 females; 576 acute and 78 staggered/chronic ingestions. In 420 (64%) acetylcysteine was stopped for low-risk paracetamol concentrations. An adverse reaction occurred in 229/654 admissions (35%; 95% CI: 31–39%): 173 (26.5%; 95% CI: 23–30%) only gastrointestinal, 50 (8%; 95% CI: 6–10%) skin only systemic hypersensitivity reactions; and three severe anaphylaxis (0.5%; 95% CI: 0.1–1.5%; all hypotension). Adverse reactions occurred in 111/231 (48%) receiving full treatment compared to 116/420 (28%) in whom the infusion was stopped early (absolute difference 20%; 95% CI: 13–28%; p < 0.0001). In 200 overdoses < 10 g, one had toxic paracetamol concentrations, but 53 developed reactions. Sixteen patients had an ALT > 1000 U/L and 24 an abnormal ALT attributable to paracetamol; all but one had treatment commenced >12 h post-ingestion.Conclusion : A 2-phase acetylcysteine infusion protocol results in a fewer reactions in patients with toxic paracetamol concentrations, but is not justified in patients with low-risk paracetamol concentrations.